Cernavoda Tritium Removal Facility—Evolution in TRF Design. (3rd April 2017) - Stefan, L.; Trantea, N.; Roberts, A.; Strikwerda, S.; Antoniazzi, A.; Zaharia, D.
Abstract: ICSI has recently completed the conceptual design of the Cernavoda Tritium Removal Facility (CTRF). CTRF is sized to process heavy water from 2 CANDU reactors, treating 40 kg/h of 10–54 Ci/kg heavy water over 40 years. CTRF removes tritium using Liquid Phase Catalytic Exchange (LPCE) paired with Cryogenic Distillation (CD). The CTRF design has implemented improvements based on design and operational knowledge from DTRF, WTRF, ICSI pilot plant, other tritium laboratories, and industry. Additionally, there are site, client, and regulatory requirements that have imposed differences from other TRF designs. This paper identifies the key improvements and requirements, explains the rationale for the design choice and highlights drawbacks. The key improvements and requirements, grouped under four categories, include: Safety – a Safe Shutdown State, higher seismic qualifications, restrictions on D2 O transfers, extensive use of double containment; Core Systems – use of a mixed catalyst bed for the LPCE, no catalytic oxidation skid, helium refrigeration system cooling of the cryoadsorbers, better control of the CD cascade by using pumps on reverse flows, and the use of a CuO reactor with molecular sieves dryers for cleanup of tritium in glovebox atmospheres; Site, client and regulatory requirements – lower worker dose limits, independent utilities from nuclear Units 1 and 2, different targets for environmental releases and management of external hazards, and the application of the latest reactor grade Regulatory Standards in force in Romania; Auxiliary systems, utilities, and the building – removal of H2 -O2 recombiner catalyst from the Air Detritiation System, use of a PEM electrolytic cell for D2 makeup, and no need for steam in the CTRF facility.